2020
DOI: 10.1111/bpa.12877
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal apneic phenotype in a murine congenital central hypoventilation syndrome model is induced through non‐cell autonomous developmental mechanisms

Abstract: Congenital central hypoventilation syndrome (CCHS) represents a rare genetic disorder usually caused by mutations in the homeodomain transcription factor PHOX2B. Some CCHS patients suffer mainly from deficiencies in CO2 and/or O2 respiratory chemoreflex, whereas other patients present with full apnea shortly after birth. Our goal was to identify the neuropathological mechanisms of apneic presentations in CCHS. In the developing murine neuroepithelium, Phox2b is expressed in three discrete progenitor domains ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Immunofluorescence (IF) staining of mouse brain sections was performed as previously described ( 31 ). Slides were washed 3 times for 15min with PBS to remove residual OCT.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence (IF) staining of mouse brain sections was performed as previously described ( 31 ). Slides were washed 3 times for 15min with PBS to remove residual OCT.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been shown that mutant Phox2b may induce secondary/non-cell autonomous defects of key brainstem respiratory neurons (Alzate-Correa et al, 2020). Indeed, the expression of NPARM PHOX2B mutation in Phox2b + nonrespiratory progenitor cells such as visceral motor neuron progenitors, induced a severe neonatal apnea along with a significant loss of neurons directly deriving from that specific progenitor domain but also from respiratory neural structures, such as RTN and preBötC, embriologically unrelated to that progenitor domain.…”
Section: Developmental Defects In Mouse Genetic Models and Cchs Patientsmentioning
confidence: 99%
“…Our finding of a dysgenesis of the hypoglossal nucleus thus showed that the Phox2b 27Ala /+ mutation elicits non-cell-autonomous mechanisms affecting respiratory networks. To date, such mechanisms were only reported in newborn mice with a non-polyalanine repeat mutation (the frameshift Phox2BΔ8 mutation), which expressed a dysfunctional preBötzinger complex, a non- Phox2b dependent brainstem site that is responsible for respiratory rhythmogenesis (33). Taken together, therefore, these findings widen the range of possible respiratory control disorders caused by Phox2b mutations.…”
Section: Discussionmentioning
confidence: 99%